Impact of single and double infection with cucumber mosaic virus and potato virus Y on growth and yield of pepper - Arogundade, O.; Balogun, O.S.; Goodness, A.U.; Kumar, P. Lava (Informa UK Limited, 2019)
Pepper (Capsicum spp. L.) production is constrained by Cucumber mosaic virus (CMV) and Potato virus Y (PVY). Local pepper varieties may confer some degree of resistance against these viruses which needs to be evaluated. A screen house study using potted plants was carried out to determine performance of pepper accessions in response to single, and double, inoculation with CMV and PVY. The accessions were inoculated at 4 weeks after planting and growth and yield components recorded. Virus detection and quantification were with antigen-coated plate enzyme-linked immunosorbent assay, which also provided resistance classification. The accessions were rated based on loss incurred in growth and yield. Pepper accessions receiving no viral treatment generally performed better than viral infected plants. Accessions inoculated with CMV were most severely affected, followed by accessions inoculated with CMV+PVY. Pepper accessions inoculated with PVY had higher values than CMV infested accessions for plant height, number of leaves and number of branches but lower values for yield. Accession NCR/AA/MAY/09/051 is classified as very tolerant while accessions NCR/AA/MAY/09/013, NCR/TB/OCT/09/006, NCR/MR/MAY/09/021 are classified as moderately tolerant. For the mixed infection, all accessions were classified as very susceptible. Some accessions exhibited some level of tolerance and may be useful in the search of genotypes that could incorporate resistance.